Metabolic syndrome in children with overweight and obesity: a hospital based cross sectional study - Vijayakumar, Madhava; Balakrishnan, Ajitha; Pillai, Sabitha Sasidharan (International Journal of Contemporary Pediatrics, 2024)
Background: Objective of the research was to study metabolic syndrome (MS) in children with overweight and obesity. Methods: A cross sectional descriptive study was carried out on 264 children aged 3-16 years with overweight and obesity attending the endocrinology clinic of a tertiary care hospital in South India from January 2016 to March 2018. Children with and without MS were compared. Results: Out of 264 children with overweight or obesity, 80 had MS (30.3%). Among children with obesity, proportion of patients with MS (40.5% versus 24.2%, p=0.012), hypertriglyceridemia (54.8% versus 37.5%, p=0.013), low high density lipoprotein cholesterol (HDL-C) (42.9% versus 28.1%, p=0.027) and dyslipidemia (78.6% versus 59.4%, p=0.004) were higher among girls versus boys. Proportion of patients with elevated systolic blood pressure (BP) (18.8% versus 4.3%, p<0.0001), elevated diastolic BP (34.5% versus 5.4%, p<0.0001), impaired fasting glucose (16.2% versus 7.6%, p=0.033), hypertriglyceridemia (85% versus 26.6%, p<0.0001), low HDL-C (75% versus 15.2%, p<0.0001) and dyslipidemia (97.5% versus 57.1%, p<0.0001) were higher in those with MS versus those without. Conclusions: MS noted in younger children with overweight and obesity in the current study is concerning as these children are at increased risk for hypertension, type 2 diabetes and cardiovascular disease in early adulthood leading to huge economic burden on the country. It is therefore of utmost importance to take necessary steps to identify these children, manage obesity effectively before MS sets in and initiate preventive measures thereby ensuring a healthy young generation in the coming years.